Unmarried Mother's Knowledge and Attitudes toward Emergency Contraceptive Pills - Gyeong Mi Lee; Hyo Jung Koh; Hye Young Kim (Korean Society of Women Health Nursing, 2013)
PURPOSE: This study was conducted to identify relationships among knowledge and attitudes of unmarried mothers toward emergency contraceptive pills. METHODS: Data were collected through structured questionnaires from 135 unmarried mothers enrolled in 7 single mothers' facilities nationwide. Data were analyzed using the SPSS/WIN 17.0 program for descriptive statistics, t-test, ANOVA, Scheffe-test, and Pearson correlation coefficients. RESULTS: For knowledge about emergency contraceptive pills, there were significant differences among who live with her before pregnancy, experience of past pregnancies, state of present pregnancy and preparation in using contraceptives. For attitude toward emergency contraceptive pills, there were significant differences according to age, education level and religion. There were significant positive relationships between knowledge and attitudes toward emergency contraceptive pills. CONCLUSION: The results of this study suggest that unmarried women should be better informed about emergency contraceptive pills, and reassured about their safety. Efforts are needed to disseminate up-to-date information to experts in sex education including nurses.